Association between Educational Level and Nomophobia and Its Mental, Physical, and Social Health Implications: A Cross-Sectional Study - Wiyatno, Eko Rustamaji; Wijayanti, Dyah; Dinarwiyata, Dinarwiyata (Chakra Brahmanda Lentera Institute, 2026)
Background: Nomophobia has emerged as a growing public health concern due to excessive smartphone dependence and its adverse effects on mental, physical, and social well-being. Although various interventions have been developed to address Nomophobia, evidence regarding the influence of educational background on Nomophobia and its associated health consequences remains limited. This study examined the association between educational background and nomophobia and its mental, physical, and social health outcomes. Methods: A cross-sectional study was conducted among 392 participants, purposively recruited from individuals with diploma- to doctoral-level educational attainment. Nomophobia was assessed using a modified version of the Nomophobia Questionnaire (NMP-Q), with responses converted from a 7-point to a 3-point Likert scale. Because the NMP-Q does not assess physical and social health outcomes, additional self-reported questionnaires were developed to measure these domains. Data were analyzed using multinomial logistic regression using IBM SPSS Statistics version 23, with statistical significance set at p < 0.05. Results: Nomophobia was observed across all educational levels (p < 0.001). Educational background was significantly associated with the mental (p = 0.017), physical (p = 0.001), and social (p = 0.014) health consequences of Nomophobia. Furthermore, higher educational attainment was significantly associated with a lower likelihood of experiencing Nomophobia and its related mental, physical, and social health problems (p < 0.001). Conclusion: Educational background was significantly associated with nomophobia and its mental, physical, and social health consequences. Individuals with higher educational attainment were less likely to experience Nomophobia and its adverse health outcomes. These findings highlight the importance of integrating digital health literacy and responsible smartphone-use education into health promotion strategies to reduce the burden of Nomophobia across diverse educational groups.